Screening for Postpartum Depression and Associated Factors among Women who Deliver at a University Hospital, Nepal. - Kunwar, D; Corey, EK; Sharma, P; Risal, A (Kathmandu University Medical Journal, 2015)
Background Postpartum depression (PPD) is a neglected area of maternal health care in developing countries like Nepal; not only in the treatment aspect, but also, in the areas of research. However, it is important to identify and treat postpartum depression because it can have grave consequences for both the mother and her children.Objective To determine the screening prevalence and risk factors of postpartum depression, among women who deliver at university hospital Nepal.Method This is a cross-sectional study investigating the relationship between postpartum depression and various factors. A total of 100 postpartum women who presented to a Dhulikhel hospital for delivery were interviewed on days 2-3 after delivery. The mothers were administered Edinburgh Postnatal Depression Scale (EPDS) as well as a proforma that included questions about the known risk factors (sociodemographic and sociocultural factors, and mother-related, pregnancy-related, and child related factors).Result The overall screening prevalence of depressive symptoms in the postnatal period (defined as EPDS=>13) was 29 %( 95% CI 20.1%-37.8%). On univariate analysis (chi square test), postpartum depression was significantly associated with pregnancy complications (p